Kratka proza na prelomu tisočletja - Žbogar, Alenka (Jezik in slovstvo, 2005)
A review of Slovene short stories and short novels written in the last two decades of the twentieth century illustrates that the eighties are more prominently marked by production of short stories rather than short novels, while quite the opposite holds true of the nineties, when short novels seem to predominate. A comparison between the narration of the so-called great themes by Andrej Blatnik and Drago Jančar reveals that the new and the young Slovene prose works differ in their conceptualisation, although both generations frequently portray the (superficial) interpersonal relationship in the urban milieu, and both also employ lyrical aspects and intimism. Fantasy elements are traditional for the older generation, and re-interpretative for the younger writers. New Slovene prose also employs folk motifs with fairytale elements; typical especially of young Slovene prose is a significant shift to meta-fiction.
Keywords: 1980/2000; kratka proza; literarne študije; Slovene literature; slovenska književnost